PENINGKATAN KUALITAS GABAH DENGAN PROSES PENGERINGAN MENGGUNAKAN ZEOLIT ALAM PADA UNGGUN TERFLUIDISASI - Rohmat Figiarto; Sheila Luvi Galvani; M. Djaeni (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
One of problem in paddy production in Indonesia is at paddy grain drying process. This far, farmers in indonesia are very dependent on sun rays to dry their paddy grain, therefore, when the rain season comes, they find it hard to dry it. Also, the quality of sun drying is considered low. The goals of this research are to dry paddy grain in fluidized bed using natural zeolite to make drying process faster, to obtain the effect of operation condition to drying process, and to obtain the effect of operation condition to paddy quality. the  condition operation in this research are air temperatures (30, 40, 50, 60C), air velocity (1.5, 2, 2.5, 3 m/s),  and rasio of paddy grain to zeolite (0%, 20, 40, 60% zeolite).  this research are done by drying paddy grain in fluidized bed  in certain time until the moisture content of paddy grain  is 12 - 14%. The result of this research are as follow: at 30C Nc = 0.0054, at 60C Nc = 0.012. air velocity at 1.5 m/s  Nc = 0.0071, where at 3 m/s Nc = 0.0115. Non zeolit variable  Nc = 0.0051, where at 60% zeolite, Nc = 0.0068. From these data, we can conclude that as the air temperature, air velocity and %w zeolite increase, the drying rate will increase therefore drying process takes shorter time. The best quality of dry paddy grain is produced when the air temperature is 40C. The increasity of air velocity %w zeolite can improved the quality of paddy grain.